2005
DOI: 10.1161/01.str.0000176743.67564.5d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Treatment With Pravastatin on Cerebral Vasospasm, Autoregulation, and Delayed Ischemic Deficits After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Statins may improve cerebral vasomotor reactivity through cholesterol-dependent and -independent mechanisms. A phase II randomized controlled trial was conducted to examine the hypothesis that acute pravastatin treatment could improve cerebrovascular autoregulation and reduce vasospasm-related complications after aneurysmal subarachnoid hemorrhage (SAH). Methods-A total of 80 aneurysmal SAH (aSAH) patients (18 to 84 years of age) within 72 hours from the ictus were randomized equally to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
330
0
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 387 publications
(347 citation statements)
references
References 29 publications
6
330
0
10
Order By: Relevance
“…In 2005, Lynch et al 42 found that simvastatin (80 mg daily for 14 days) reduced the incidence of vasospasm and biomarker surrogates of endothelial dysfunction and CNS inflammation. These results were concordant with the study by Tseng et al, 75 who demonstrated that pravastatin (40 mg daily for 14 days) improved surrogate measures of vasospasm and functional outcomes. Two other small prospective studies also demonstrated safety and feasibility of statin use in SAH, but did not show statistically significant improvement in vasospasm, delayed ischemic deficit, or functional outcomes.…”
Section: Clinical Experience With Statins For the Treatment Of Acute supporting
confidence: 91%
See 1 more Smart Citation
“…In 2005, Lynch et al 42 found that simvastatin (80 mg daily for 14 days) reduced the incidence of vasospasm and biomarker surrogates of endothelial dysfunction and CNS inflammation. These results were concordant with the study by Tseng et al, 75 who demonstrated that pravastatin (40 mg daily for 14 days) improved surrogate measures of vasospasm and functional outcomes. Two other small prospective studies also demonstrated safety and feasibility of statin use in SAH, but did not show statistically significant improvement in vasospasm, delayed ischemic deficit, or functional outcomes.…”
Section: Clinical Experience With Statins For the Treatment Of Acute supporting
confidence: 91%
“…87 However, neuroprotection has been demonstrated even with hydrophilic statins, such as rosuvastatin 67 and pravastatin, 75 presumably due to vascular and anti-inflammatory effects, although breach of the BBB is common after acute brain injury. In fact, the pilot trials evaluating statins in SAH used both lipophilic and hydrophilic statins (simvastatin 42 and pravastatin, 75 respectively), with a similar decrease in cerebral vasospasm. It is not known whether potency or the ability of a particular statin to lower cholesterol is important in the setting of neuroprotection.…”
Section: Clinical Trial Designs For Statins In Tbimentioning
confidence: 99%
“…The results of these trials were impressive, as acute statin treatment decreased the incidence of not only vasospasm, but also of DCI and mortality (Lynch et al, 2005;Tseng et al, 2005Tseng et al, , 2007. Statins may be an interesting treatment option in patients with SAH as statins possibly not only decrease the incidence of vasospasm, but also reduce plasma levels of vWF, indicating decreased endothelial activation (Lynch et al, 2005;Tseng et al, 2005). Furthermore, statins have been shown to enhance fibrinolysis and inhibit blood coagulation (Krysiak et al, 2003).…”
Section: Studies Investigating Drugs To Prevent Delayed Cerebral Ischmentioning
confidence: 99%
“…It has been described that cerebral autoregulation may become disturbed after subarachnoid hemorrhage (SAH), [1][2][3][4][5][6][7] which has been associated with development of delayed cerebral ischemia (DCI). 1,2,[5][6][7][8][9] The transient hyperemic response test (THRT) is a transcranial Doppler (TCD) based method, which characterizes the changes in cerebral blood flow velocity (FV) after a brief compression of the common carotid artery. It is a recognized and simple method of testing autoregulation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It is a recognized and simple method of testing autoregulation in vivo. 2,6,8,[10][11][12][13][14][15][16][17][18] It is directly proportional to the static rate of autoregulation, which is the 'gold standard' for measuring autoregulation, 15 and it has been shown to be predictive of DCI after SAH. 2,6 However, other ways of measuring autoregulation that do not require physical or pharmacological blood pressure stimulation have been described.…”
Section: Introductionmentioning
confidence: 99%